Cancellation of Regional Head Candidates by Bawaslu in Simultaneous Regional Head Elections in Tasikmalaya Regency in 2020 - Mohammad Iqbal Alam Islami; Valina Singka Subekti (Universitas Medan Area, 2023)
The aim of the study was to analyze the Cancellation of Regional Head Candidates by Bawaslu in the Simultaneous Pilkada in Tasikmalaya Regency in 2020. The method used in this research is qualitative with a case study approach. The subjects in this study were people who were directly involved in the 2020 regional elections for Tasikmalaya Regency. The results showed that referring to the Tasikmalaya Regency Bawaslu Letter Number 046/K.Bawaslu.JB-18/PM.00.02/XXII/2020. The incumbent uses his authority to influence voters by issuing the District Head's Instruction Letter No. 6 of 2020 September 2 2020 concerning the Acceleration of Waqf Land Certification in Tasikmalaya Regency addressed to sub-district heads throughout Tasikmalaya Regency and district head circular letter Number 42 of 2020 dated September 3 2020 addressed to MUI Tasikmalaya Regency, Chair of BKPRMI Tasikmalaya Regency and Chair of the Islamic Boarding School Forum Tasikmalaya Regency. There is no charge/free of charge for land issuance administration fees. But the Tasikmalaya Regency KPU study found no violations. It was later proven that Bawaslu member Ahmad Aziz Firdaus had abused his authority, was unprofessional and was involved in a conflict of interest because Firdaus' wife had a sibling relationship with the wife of Iip Miftahul Faoz.